Vicious circle in power sector (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Not available.DOI: 10.3126/hn.v7i0.4221Hydro Nepal Journal of Water, Energy and EnvironmentVol 7, July, 2010 Page: 8 Uploaded Date: 28 January, 2010